Urinary cMet as a prognostic marker in immunoglobulin A nephropathy. Issue 19 (21st August 2020) - An, Jung Nam; Li, Lilin; Lee, Junghun; Yu, Seung‐Shin; Kim, Jin Hyuk; Lee, Jeonghwan; Kim, Yong Chul; Kim, Dong Ki; Oh, Yun Kyu; Lim, Chun Soo; Kim, Yon Su; Kim, Sunyoung; et al.
Abstract: The prediction of prognosis in patients with immunoglobulin A nephropathy (IgAN) is challenging. We investigated the correlation between urinary cMet (ucMet) levels and clinical parameters and examined the effects of cMet agonistic antibody (cMet Ab) in an in vitro IgAN model. Patients diagnosed with IgAN (n = 194) were divided into three groups representing undetectable (Group 1), below‐median (Group 2) and above‐median (Group 3) levels of ucMet/creatinine (ucMet/Cr). Stained kidney biopsy samples were graded according to cMet intensity. Primary‐cultured human mesangial cells were stimulated with recombinant tumour necrosis factor (TNF)‐α and treated with cMet Ab. Our results showed that ucMet/Cr levels positively correlated with proteinuria ( P < .001). During the follow‐up, patients in Group 3 showed a significantly lower probability of complete remission (CR; uPCr < 300 mg/g) than those in groups 1 and 2, after adjusting for blood pressure, estimated glomerular filtration rate, and proteinuria, which influence clinical prognosis (HR 0.60, P = .038); moreover, ucMet/Cr levels were also associated with glomerular cMet expression. After TNF‐α treatment, the proliferation of mesangial cells and increased interleukin‐8 and intercellular adhesion molecule‐1 expression were markedly reduced by cMet Ab in vitro. In conclusion, ucMet/Cr levels significantly correlated with proteinuria, glomerular cMet expression, and the probability of CR. Further, cMet Ab treatment alleviated the inflammation and proliferation of mesangial cells. Hence, ucMet could serve as a clinically significant marker for treating IgAN.